1997
DOI: 10.1111/j.1365-2923.1997.tb02470.x
|View full text |Cite
|
Sign up to set email alerts
|

Interviewing skills: self-evaluation by medical students

Abstract: In an independent learning project, 52 third-year medical students carried out a structured self-assessment of two videotaped psycho-social interviews they had conducted with volunteer clients 1 year earlier, as part of a previous course. The interviews had been conducted in small tutorials with feedback from their clients, fellow students and tutors, facilitated by videotape playback. During the sequence of 16 tutorials each student had carried out an early and a late interview and had observed and participat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
2

Year Published

2002
2002
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 24 publications
0
20
0
2
Order By: Relevance
“…Extensive use of clear benchmarks, unambiguous standards, and explicit training with feedback has been shown to improve self-assessment (Woolliscroft et al, 1993). Reviewing self-performance at different times may produce discriminations that escape isolated, independent judgment (Farnill, Hayes, & Todisco, 1997) though our study suggests that this may have to be done in a structured manner. While self-assessment is often inaccurate, medical students' evaluations of peers have been shown to be more consistent with faculty assessments than their own self-assessments (Morton & Macbeth, 1977;Sullivan, Hitchcock, & Dunnington, 1999).…”
Section: Discussionmentioning
confidence: 82%
“…Extensive use of clear benchmarks, unambiguous standards, and explicit training with feedback has been shown to improve self-assessment (Woolliscroft et al, 1993). Reviewing self-performance at different times may produce discriminations that escape isolated, independent judgment (Farnill, Hayes, & Todisco, 1997) though our study suggests that this may have to be done in a structured manner. While self-assessment is often inaccurate, medical students' evaluations of peers have been shown to be more consistent with faculty assessments than their own self-assessments (Morton & Macbeth, 1977;Sullivan, Hitchcock, & Dunnington, 1999).…”
Section: Discussionmentioning
confidence: 82%
“…Le fait que les étudiants n'admettent pas un déficit en matière de techniques de communication peut constituer un obstacle à la mise en place d'un enseignement dédié à ces dimensions. Les études montrent d'ailleurs que les auto-évaluations par les étudiants sont faiblement corrélées avec les évaluations externes [21][22][23] et que les connaissances théoriques en TC ne permettent pas une communication réussie avec les patients. Ces données de la littérature remettent en cause la réalité des capacités des étudiants libanais en matière de communication et plaident en faveur d'études ultérieures comportant une évaluation par des tiers, ainsi que des éva-luations de la satisfaction des patients.…”
Section: Discussionunclassified
“…The validity and accuracy of student assessments have also been questioned, particularly self-assessments of performance. [17][18][19][20][21][22][23][24][25] A recent literature review on physician self-assessment that excluded studies of medical students concluded that the ability of physicians to assess their performance is limited. 25 In contrast, most studies of medical students suggest that their ability to accurately selfevaluate their performance is moderately good, particularly in the clinical domains included in our survey.…”
Section: Figmentioning
confidence: 99%
“…25 In contrast, most studies of medical students suggest that their ability to accurately selfevaluate their performance is moderately good, particularly in the clinical domains included in our survey. [17][18][19][20][21][22][23] Female student ratings were lower than those of their male colleagues, particularly in their assessment of the extent to which topics were integrated into curricula, and they were more likely to request additional sex/gender-specific teaching. Reasons for the disparity are uncertain but may reflect gender differences in students' knowledge, educational expectations, or perceptions about the importance of certain topics.…”
Section: Figmentioning
confidence: 99%